Optimization of management in women with traumatic perineal injuries - Грищенко, О. В.; Лахно, И. В. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
It was performed a study of the effectiveness of vaginal suppositories Depantol application for the treatment of women with perineal trauma. It was examined 124 patients after vaginal delivery and 94 from them had perineal tears of I–II degree. In the main group consisted of 48 mothers with perineal tears it was administered Depantol 1 suppository intravaginally daily for 10 days. In the women with perineal lesions it was marked an increase of pro-inflammatory cytokines and CRP level. It was associated with the inflammatory response and could contribute to the formation of fibrotic scars. On the 3 day examination it was found that hyperemia of the wound was absent in all parturients of the main group and in the comparison group it was noted in 37,0% of cases. The complete epithelization of the wound of the perineum has occurred on 7,5 ± 1,4 days in case of Depantol treatment and 11,2 ± 3,8 day in parturients of the comparison group. The usage of Depantol has allowed realizing a friendly approach to management of women with perineal tears confirmed by its clinical efficacy